Reflexive City: use of rainwater to improve the technological quality of urban open spaces - Violano, Antonella (2019)
This contribution presents the results of a complex interdisciplinary research on the theme of the “reflexive city”, which interacts emotionally with its inhabitants and makes readable and understandable the archetypes of public space. It is a technological reading, aimed to offer a methodological approach for the meta-design phase of the transformation process in a historical context. Via Sopramuro in Pendino neighbourhood in Naples is the case of study. In this urban area, the eco-oriented analyses, carried out according to the RUROS method, show that it is a strategic place to preserve the historical market activities, improving environmental quality with an appropriate technological design as added value. It follows the sustainable design principles especially related to the water sources saving, as a part of a most complex urban design integrating strategies in order to improve the visual quality of this urban space. The expected result is not only the design response in a technological key, but the hypothesis of reproducibility and adaptability of this model to urban transformation process also to other sites in the Mediterranean area.